2014
DOI: 10.1021/ph500201b
|View full text |Cite
|
Sign up to set email alerts
|

Mode Control of Random Laser Action Assisted by Whispering-Gallery-Mode Resonance

Abstract: Whispering-gallery-mode (WGM) resonance manipulated random laser action has been proposed. To illustrate our working principle, lasing characteristics of ZnO nanorods decorated with SiO2 nanospheres have been investigated. It is found that with the assistance of SiO2 nanospheres the emission spectrum exhibits a very narrow background signal with a few sharp lasing peaks and a very small full width at half-maximum of less than 0.3 nm. The differential quantum efficiency (ηd) of random laser action can be greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…It has been reported that random lasings (RLs) are generated by WGM resonance in disordered systems. Chen et al [19] modified SiO 2 nanospheres on the surface of ZnO nanorods, pumping out random laser light with the aid of WGM resonance effect of spherical particles. As for a glass capillary, WGM resonance easily occurs in the wall of the capillary if the refractive index (RI) of the filling medium in the capillary is greater than the RI of the glass capillary.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that random lasings (RLs) are generated by WGM resonance in disordered systems. Chen et al [19] modified SiO 2 nanospheres on the surface of ZnO nanorods, pumping out random laser light with the aid of WGM resonance effect of spherical particles. As for a glass capillary, WGM resonance easily occurs in the wall of the capillary if the refractive index (RI) of the filling medium in the capillary is greater than the RI of the glass capillary.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Many efforts have been devoted to develop random lasers, and optically pumped random lasers have been reported extensively. [7][8][9][10][11][12][13] Realizing electrically pumped lasing has been one of the most challenging issues of random lasers, and zinc oxide (ZnO) has been considered as one of the most active materials for electrically pumped random lasers. [14][15][16][17][18][19] Although many reports have demonstrated electrically pumped random lasing from ZnO, most of them are realized in metal-insulator-semiconductor (MIS) structures.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the optical processes associated with various reasonable micro/nano cavities, such as photonic crystals cavity, Fabry–Perot (F–P) optical cavity, and whispering-gallery-mode (WGM) resonator have been considered as an attracting platform for micro or nanolaser systems . Amidst them, the WGM induced laser action is of present scrutiny by the reason for inherently high quality ( Q ) factor, small mode volume, low-lasing threshold, and relatively simple fabrication . One of the advantages of WGM oscillations arises from the underlying working principle of the strong coupling between confined light beam and the cavity.…”
mentioning
confidence: 99%
“…17 Amidst them, the WGM induced laser action is of present scrutiny by the reason for inherently high quality (Q) factor, small mode volume, low-lasing threshold, and relatively simple fabrication. 18 One of the advantages of WGM oscillations arises from the underlying working principle of the strong coupling between confined light beam and the cavity. Attributable to the total internal reflections (TIRs) of light at the hexagonal or circular boundary, there exists possibility of high-quality factor (Q) of WGMs, which enables low threshold microcavity lasers.…”
mentioning
confidence: 99%
See 1 more Smart Citation